Knowledge and perception of fluoride in drinking water among residents of Precinct 9, Putrajaya, Malaysia - Fatin Nor Athirah Yahaya,; Shaharuddin Mohd Sham,; Vera Yulyani, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The knowledge and beliefs on the presence of fluoride in drinking water, its purpose and the associated health risks aids in equate water fluoridation and effective prevention programs. Water fluoridation is a safe, effective, and necessary method where adequate doses of fluoride is added into drinking water supplies with the target of assisting in tooth restoration and preventing tooth decay and dental caries. Therefore, this study identifies the level of knowledge and perception of fluoride in drinking water among residents living in Precinct 9, Putrajaya Methods: A cross-sectional, self-administered online questionnaire was used to examine knowledge and perception of fluoride in drinking water of 240 Precinct 9 residents. Descriptive analysis was applied for socio-demographic data and Chi-square was used to compare discrete data. All data obtained were further analyzed using SPSS Version 23.0. Results: The highest frequency (percentage) of residents were 213 (88.8%), aged 18-64 years old, 141 (58.8%) female, 214 (89.2%) with tertiary education background and 125 (51.1%) of them lived in Precinct 9 for more than 10 years. Of all participants, 137 (57.1%) and 83 (34.6%) have poor knowledge and medium perception regarding fluoride in drinking water respectively. There was a significant association between those with higher education level with knowledge (p=0.02) and perception (p=0.005) where they were more likely to know about overall fluoride in drinking water. Conclusion: Most participants had limited knowledge and negative perception of fluoride beyond a general sense it was beneficial. It appears that in moving forward to receive the water fluoridation support will need to attend to the challenge of anti-fluoride sentiment influence.